Kedudukan Laporan Akhir Hasil Pemeriksaan (LAHP) Ombudsman Ditinjau Dari Fiqih Siyasah dan Undang-Undang - Imam Thohari (Universitas Islam Negeri Raden Fatah Palembang, 2023)
Maladministration cases that often occur can harm a number of people. Therefore, it is necessary to have an agency that specifically accepts reports on these matters, namely the Ombudsman of the Republic of Indonesia. In the process, the report will be concluded in the Final Examination Results Report (LAHP) regarding whether or not the case is proven. This study aims to examine the position of the Final Examination Report Report (LAHP) in the Siyasah Fiqh and Law Number 37 of 2008 concerning the Ombudsman of the Republic of Indonesia. The formulation of the problem is how is the Position of the Ombudsman Final Examination Report (LAHP) in terms of Fiqh Siyasah and Law Number 37 of 2008 concerning the Ombudsman of the Republic of Indonesia? The type of research used in this study is empirical. While the approach used in this study is the Sociological Legal Approach (Sociological Juridical). This research was conducted through interviews and study of documents, files and annual reports as well as books and other related documents. The research location is the Ombudsman Representative of South Sumatra. The results of the study concluded that first, in terms of the Fiqh Siyasah Ombudsman, it is included in the Wilayatul Hisbah which is obliged to uphold 'Amr Ma'ruf Nahi Munkar among public service providers. Second, the position of the LAHP in review based on the law has been recognized by the state and must be carried out by the reported party or the reported superior based on the hierarchy of laws in force in Indonesia.